2023
DOI: 10.3390/biomedicines11061525
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Ecological Factors Modulate the Incidence of Anti-NMDAR Encephalitis—A Systematic Review

Abstract: Anti-NMDAR encephalitis has been associated with multiple antigenic triggers (i.e., ovarian teratomas, prodromal viral infections) but whether geographic, climatic, and environmental factors might influence disease risk has not been explored yet. We performed a systematic review and a meta-analysis of all published papers reporting the incidence of anti-NMDAR encephalitis in a definite country or region. We performed several multivariate spatial autocorrelation analyses to analyze the spatial variations in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 104 publications
0
2
0
Order By: Relevance
“…5 In a mixed cohort comprising adults and children, Gopaul et al 7 linked the seasonal differences with AEs that have a higher reported prevalence in summer-autumn and in warmer months. 18,19 However, data from a Danish AE register did not suggest a strong seasonality of antibody detection in Denmark making a direct and substantial link between the seasonality of NORSE and AE less likely. It is a limitation that we used antibody positivity and not clinical diagnoses for this study and that the awareness of AE was lower before approximately 2010.…”
Section: Discussionmentioning
confidence: 99%
“…5 In a mixed cohort comprising adults and children, Gopaul et al 7 linked the seasonal differences with AEs that have a higher reported prevalence in summer-autumn and in warmer months. 18,19 However, data from a Danish AE register did not suggest a strong seasonality of antibody detection in Denmark making a direct and substantial link between the seasonality of NORSE and AE less likely. It is a limitation that we used antibody positivity and not clinical diagnoses for this study and that the awareness of AE was lower before approximately 2010.…”
Section: Discussionmentioning
confidence: 99%
“…Like several other autoimmune disorders, such as multiple sclerosis (Koch-Henriksen & Sørensen, 2010), AE and PNS display some geographical variations, which have been attributed to both genetic and environmental factors (Alentorn et al, 2023;Binks et al, 2018;Mueller et al, 2018;Titulaer et al, 2013).…”
Section: Introductionmentioning
confidence: 99%